Assessing The COBIT Maturity Model in Manufacturing Company - Johanes Fernandes Andry; Gunawan Wang; I Gusti Ngurah Suryantara; Devi Yurisca Bernanda (IJNMT (International Journal of New Media Technology), 2018)
PT Hema Indonesia is manufacturing company established in 2001 and has continued to grow. Nowadays the company has supported business processes in various companies, such as the use of information systems. The purpose of this research is to get an overview of the performance of information systems in order to determine the extent of maturity level which is currently running, with a few aspects to consider such as effectiveness and, efficiency. Implementing IT governance, however, is a challenge to organizations. To ensure IT alignment with business goals use standard COBIT. The analytical tool used is the standard procedure COBIT issued by ISACA. In this paper the method to be used is COBIT 4.1. Coverage of Audit IT Domain are Plan Organize (PO), such as PO4, PO5, PO7 and PO8. The conclusion that can be drawn from the research that has been done is IT governance at the company has been done, although still run optimally within each IT process contained in the sub domain average on level repeatable and defined proses.